2022
DOI: 10.1029/2021wr031871
|View full text |Cite
|
Sign up to set email alerts
|

On the Uncertainty Induced by Pedotransfer Functions in Terrestrial Biosphere Modeling

Abstract: Terrestrial ecosystem and ecohydrological models are of paramount importance for understanding and quantifying the coupled water and carbon cycles. Despite their physics-based modeling approach, several sources of uncertainties affect the robustness of their predictions (e.g., Fisher et al., 2014;Zhou et al., 2018). Uncertainties include epistemic sources due to specific model formulations (e.g., Schwalm et al., 2019) and poorly known model parameters (e.g., Pappas et al., 2013) due to the lack of high fidelit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 109 publications
(198 reference statements)
1
10
0
Order By: Relevance
“…Higher concentrations of MaP in this review tended to reduce K s , as reported previously by de Souza Machado et al (2018) and Guo et al (2022). Additionally, MaP reduced the soil infiltration rate and wetting front (Wen et al 2022).…”
Section: Saturated Hydraulic Conductivitysupporting
confidence: 85%
See 2 more Smart Citations
“…Higher concentrations of MaP in this review tended to reduce K s , as reported previously by de Souza Machado et al (2018) and Guo et al (2022). Additionally, MaP reduced the soil infiltration rate and wetting front (Wen et al 2022).…”
Section: Saturated Hydraulic Conductivitysupporting
confidence: 85%
“…Generally, K s is sensitive to soil bulk density (Araya and Ghezzehei 2019), suggesting that slight changes in it would greatly influence K s . With MaP and MiP, changes in K s were primarily driven by soil texture-associated structure and secondarily by plastic size distribution-associated water repellency (Wang et al 2020, Guo et al 2022. Soil water repellency is influenced primarily by soil physicochemical properties associated with organic matter content (Zema et al 2021).…”
Section: Saturated Hydraulic Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…We use the glacier component of the land‐surface model Tethys‐Chloris (Botter et al., 2021; Fatichi et al., 2012, 2021; Fugger et al., 2022; Fyffe et al., 2021; Mastrotheodoros et al., 2020; Paschalis et al., 2022) to model the surface energy balance across the glacier. The model simulates the energy fluxes of the ice/snow surface and subsurface, following: RnSNOW+QvSNOW+QfmSNOWHSNOWLESNOWGSNOWdQSNOW=0, $R{n}_{\mathit{SNOW}}+Q{v}_{\mathit{SNOW}}+Qf{m}_{\mathit{SNOW}}-{H}_{\mathit{SNOW}}-L{E}_{\mathit{SNOW}}-{G}_{\mathit{SNOW}}-d{Q}_{\mathit{SNOW}}=0,$ …”
Section: Methodsmentioning
confidence: 99%
“…We use the glacier component of the land-surface model Tethys-Chloris (Botter et al, 2021;Fatichi et al, 2012Fatichi et al, , 2021Fugger et al, 2022;Fyffe et al, 2021;Mastrotheodoros et al, 2020;Paschalis et al, 2022) to model the surface energy balance across the glacier. The model simulates the energy fluxes of the ice/snow surface and subsurface, following:…”
Section: Energy Balance Modelingmentioning
confidence: 99%